Antimicrobial Production by an Actinomycetes Isolated from The Termite Nest - Krishanti, Ni Putu Ratna Ayu; Zulfina, Deni; Wikantyoso, Bramantyo; Zulfitri, Arpiwi; Yusuf, Sulaeman (Journal of Tropical Life Science, 2018)
Actinomycetes are Gram positive bacteria that have been detected in diverse ecological niches. Their member species are known to be a main source of various bioactive compounds. The discovery of Actinomycetes from diverse and unexplored resources has also been linked to increased opportunities to obtain novel bioactive compounds. Insect nest material is being investigated as a new source of novel antimicrobial producing Actinomycetes, which could be harnessed for therapeutic potential. A total of 10 Actinomycetes isolates were collected from the nest of Nasutitermes sp. in Pananjung Pangandaran Nature Reserve. These isolates were evaluated for antimicrobial activity against the challenge bacteria (Eschericia coli, Staphylococcus aureus, Bacillus subtilis, Serratia Marcescens) and fungi (Fomitopsis palustris, Fusarium oxysporum, Trichoderma viridae) by dual culture method. The result revealed that several isolate were active against fungi and bacteria. Isolate Pn-TN2 showed the highest level of antibacterial inhibition and the highest antifungal inhibition with Inhibition Rate value more than 80%. By morphological and 16S rRNA gene sequence analysis strongly suggested that the isolate Pn-TN2 belonged to Streptomyces prasinopilosus. We suggested that termite nest is a potential source of bioactive strains of cultivable Actinomycetes for future biotechnological needs.